Standing on a sliding board affects generation of anticipatory and compensatory postural adjustments - Chen, B.; Lee, Y.-J.; Aruin, A. S. (Journal of Electromyography and Kinesiology, 2018)
Postural control is compromised in the presence of body instability. We studied anticipatory and compensatory postural adjustments people use to maintain balance while standing on an unstable surface and performing voluntary arm movements. Nine healthy participants stood on a sliding board (that was either locked and as such motionless or unlocked and as such free to move in the anterior-posterior direction) and performed fast bilateral arms flexion. Arm acceleration, bilateral electromyographic activity (EMG) of the trunk and lower extremity muscles and center of pressure (COP) displacements were recorded and analyzed within the intervals typical for the anticipatory (APAs) and compensatory (CPAs) postural adjustments. Peaks of acceleration of the arm movements were not different between the locked and unlocked conditions. Larger EMG integrals were seen in the muscles of the lower extremity in both APAs and CPAs when standing on the unlocked sliding board. No significant difference was observed in the trunk muscles. Larger maximum COP displacement was seen when participants stood on the locked board. The results demonstrated that when standing on a free to move sliding board and performing bilateral arm flexion, the central nervous system (CNS) does not slow down the arm movements; instead it modifies activation of the lower extremity muscles. The observed differences in APAs and CPAs between the locked and unlocked conditions suggest that the CNS employs similar strategy while controlling the focal part of the task and adjusts the activity of muscles that are close to the source of instability to control postural task.